2015
DOI: 10.1111/mve.12103
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of stable flies to cattle manure slurry associated odourants

Abstract: Abstract. Stable flies (Stomoxys calcitrans [Diptera: Muscidae] L.) are blood-feeding synanthropic pests, which cause significant economic losses in livestock. Stable fly antennae contain olfactory sensilla responsive to host and host environment-associated odours. Field observation indicated that the abundance of stable flies increased significantly in grasslands or crop fields when cattle manure slurry was applied. Major volatile compounds emanating from manure slurry were collected and identified. Behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 29 publications
3
30
0
Order By: Relevance
“…Our previous study on stable fly sensory physiology showed that various olfactory sensilla from stable fly antennae respond to odorants associated with cattle and their environments . Recently, we further demonstrated that several compounds from cattle manure slurry elicited behavioral responses from stable flies under field conditions . The enhanced trap catches with baited stable fly traps in this study support their future application in stable fly population reduction, as the cost of these lures is relatively low and they last over a week.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our previous study on stable fly sensory physiology showed that various olfactory sensilla from stable fly antennae respond to odorants associated with cattle and their environments . Recently, we further demonstrated that several compounds from cattle manure slurry elicited behavioral responses from stable flies under field conditions . The enhanced trap catches with baited stable fly traps in this study support their future application in stable fly population reduction, as the cost of these lures is relatively low and they last over a week.…”
Section: Discussionsupporting
confidence: 72%
“…Several studies have also shown that volatile odorants associated with hosts and their environments are used by stable flies for host seeking . Attractants may be useful for improving trap efficacy in the mass trapping of stable flies …”
Section: Introductionmentioning
confidence: 99%
“…Among them, 4‐methylphenol elicited the highest AEG voltage (4.6 mV), followed by the remaining phenolic compounds. Phenol and 4‐methylphenol have been found previously in horse and cattle manure, and cattle urine, respectively (Birkett et al ., ; Jeanbourquin & Guerin, 2007b; Tangtrakulwanich et al ., ). These two compounds have also been shown to evoke high EAG responses and to represent an effective chemical stimulant for trapping biting fly species of the Tabanidae, Calliphoridae, Sarcophagidae and Muscidae families (all: Diptera) (Krčmar, ; Baldacchino et al ., ; Tangtrakulwanich et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Phenol and 4‐methylphenol have been found previously in horse and cattle manure, and cattle urine, respectively (Birkett et al ., ; Jeanbourquin & Guerin, 2007b; Tangtrakulwanich et al ., ). These two compounds have also been shown to evoke high EAG responses and to represent an effective chemical stimulant for trapping biting fly species of the Tabanidae, Calliphoridae, Sarcophagidae and Muscidae families (all: Diptera) (Krčmar, ; Baldacchino et al ., ; Tangtrakulwanich et al ., ). 2‐Methoxyphenol and 3‐methoxyphenol in cattle host odours and cattle urine have been found to evoke electrophysiological responses in Haematobia irritans , Musca autumnalis (both: Diptera: Muscidae) and S. calcitrans (Birkett et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Stable flies preferentially oviposit in media with a robust microbial community, especially one rich in Citrobacter freundii (Romero et al ). Volatile chemostimulants from livestock manure also attract stable flies to oviposit (Jeanbourquin and Guerin , Tangtrakulwanich et al ).…”
Section: Discussionmentioning
confidence: 99%